Pengaruh Substitusi Tepung Labu Kuning (Cucurbita Moschata) Dalam Pembuatan Pancake Terhadap Kadar Β-Karoten Dan Daya Terima - Isnaini, Aan Nur, Pramudya Kurnia, STP, M.Agr, Fitriana Mustikaningrum, S.Gz, M.Sc (2016)
Introduction: The nutrition level contains in the pumpkin flour contains is not faraway different from the wheat, indeed, the level of β-carotene in the pumpkin flour is higher (180 SI/ g). β-carotene has stable characteristic in the food processing. Pancake is a pastry product made of flour which is rich of carbohydrates nutrients, and to improve the nutrients, especially β-carotene in the panceke, pumpkin flour can be used as a substituted of wheat flour. Objective: To find out the effect of pumpkin flour substitution on the levels of β- carotene and receptivity in the pancakes. Methods: The method of this study is an experimental research with a complete randomized design with 3 treatments of: (5%, 10% and 15%). The statistical analysis of the β-Carotene and receptive level was done by using One Way ANOVA with a significance level of 95% and followed by Duncan Multiple Range Test (DMRT). Results: The results obtained from the β-Carotene level test indicated that the highest β-Carotene level in the pancakes with pumpkin flour subtitution is 15%, 0.441 g/ 100 g. Based on One Way Anova statistical test of pumpkin flour substitution on the level of β-carotene indicated the value of p = 0.000. Based on the statistical test of receptivity indicated the receptivity of the color with the value of p = 0.000; aroma p = 0.000; flavor p = 0.000; texture p = 0.156; and overall fondness p = 0.024. Conclusion: There is a significant effect of the pumpkin flour subtitution on the level of β-Carotene and there is an effect of pumpkin flour subtitution in the pumpkin pancakes-making on the receptivity include color, aroma, flavor, and overall fondness and there is no effect of pumpkin flavour subtitution in the pumpkin pancake-making on the receptivity of texture. Keywords : the receptivity of pancakes, the levels of β-carotene, pumpkin flour